Gait velocity as a tool for evaluating the effects of gait training in patients with chronic stroke - Guzik, Agnieszka; Drużbicki, Mariusz; Kwolek, Andrzej; Przysada, Grzegorz; Brzozowska-Magoń, Agnieszka (European Journal of Clinical and Experimental Medicine, 2016)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Background. Gait velocity is a simple but very essential parameter which may be applied as an indicator of functional efficiency. Gait of stroke patients is characterized by reduced speed. As a result, the patients have significantly limited functioning capabilities, including walking independently outside home. The study was designed to assess selected temporal gait parameters, including gait velocity, stride velocity and swing phase velocity in patients with chronic stroke following a rehabilitation program with the use treadmill. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and method. The study was conducted in a group of 50 patients with hemiparesis in the late period after stroke. Temporal gait parameters such as: gait velocity, stride velocity and swing velocity were examined. Additionally, 10-metre walk test was measured. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. While analyzing 10-metre walk test results it was shown that after rehabilitation gait velocity increased by an average of 0.15 m/s (p = 0.0000). Similar results were obtained in terms of gait velocity which had been assessed using a 3-dimensional gait analysis, the average gait velocity increased by 0,14m/s (p = 0.0000). Analyzing stride velocity, both the paretic and non-paretic side it was noted that after rehabilitation this particular parameter increased by an average of 0.05 m/s (p = 0.0019) and 0.06 m/s (p = 0.0052). Similar results were achieved in terms of swing velocity of the paretic side - p = 0.0017. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. It was demonstrated that rehabilitation program with the use of treadmill enabled significant improvement in gait velocity, stride velocity and swing phase velocity in patients with chronic stroke. Gait velocity is a practical and simple tool to be applied for monitoring of progress in rehabilitation and for assessing effects of gait re-education in patients with hemiplegia in a chronic stage after stroke.